2009
DOI: 10.1007/s12034-009-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behaviour of spinel-alumina composites

Abstract: Study of alumina-magnesia binary phase diagram reveals that around 40-50 wt% alumina dissolves in spinel (MgAl 2 O 4 ) at 1600°C. Solid solubility of alumina in spinel decreases rapidly with decreasing temperature, which causes exsolution of alumina from spinel phase. Previous work of one of the authors revealed that the exsolution of alumina makes some interlocking structures in between alumina and spinel phases. In the present investigation, refractory grade calcined alumina and spinel powder were used to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…A lattice fringe spacing of approximately 0.22-0.30 nm was observed in the precipitated particles as shown in Fig.6 (a), which is in good agreement with those of 0.24 nm (Ag (1 1 1)) and 0.28-0.3 nm (silver oxide) in soda-lime silicate glasses [25] and silica thin films [26] with Ag particles. A qualitative composition analysis using EDXS during TEM confirmed that these spherical particles were silver nanoparticles.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…A lattice fringe spacing of approximately 0.22-0.30 nm was observed in the precipitated particles as shown in Fig.6 (a), which is in good agreement with those of 0.24 nm (Ag (1 1 1)) and 0.28-0.3 nm (silver oxide) in soda-lime silicate glasses [25] and silica thin films [26] with Ag particles. A qualitative composition analysis using EDXS during TEM confirmed that these spherical particles were silver nanoparticles.…”
Section: Resultssupporting
confidence: 80%
“…In the case of the GD-450 dosimeter used in this work, the peak intensity at 310 nm linearly increased up to 5 Gy for X-ray irradiation [24]. Similar investigations on phosphate-and silicate-based glasses containing silver have been performed by TEM analysis and various optical measurements to understand the origin of the induced bands and the mechanisms of nucleation and growth processes [18,[25][26][27][28]. Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Ag 0 nanoparticles smaller than 10 nm, such as silver colloids in water, are yellow, and exhibit a SPR absorption band at around 400 nm [63][64][65]. A yellow color has also been reported for Ag 0 particles interacting with a support [22,65,66]. Since no Ag particles are detected by XRD or TEM in our calcined samples, this means that they are smaller than 1 nm (i.e., containing less than 50 atoms).…”
Section: X-ray Diffraction and Electron Microscopysupporting
confidence: 54%
“…Since no Ag particles are detected by XRD or TEM in our calcined samples, this means that they are smaller than 1 nm (i.e., containing less than 50 atoms). Accordingly, Pal and De [65] could not observe either any nanoparticles in a yellow Ag/porous silica film calcined in air at 450 °C. Hence, the band at 350 nm and the yellow color of our samples can result from the SPR of Agn clusters, neutral or slightly positively charged and containing a small number of Ag atoms.…”
Section: X-ray Diffraction and Electron Microscopymentioning
confidence: 89%
See 1 more Smart Citation